Preparation method and application of coralline-like low-temperature rare earth-based denitration and chlorobenzene removal catalyst
By using coral-like low-temperature rare earth-based denitrification and dechlorobenzene catalyst, the problem of insufficient catalytic activity of denitrification and dechlorobenzene in the existing technology is solved, efficient flue gas treatment is achieved, and the cost is reduced. The preparation process of the catalyst is environmentally friendly and economical.
Patent Information
- Application Number
- CN202411892018.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-18
AI Technical Summary
The catalytic activity of low-temperature flue gas denitrification and dechlorobenzene catalysts in the existing waste incineration industry is insufficient, resulting in an increase in the cost of flue gas treatment.
Coral-like low-temperature rare earth-based denitrification and dechlorobenzene catalyst is used. The catalyst is prepared by ultrasonic foaming polymerization-template-hydrothermal-impregnation-impregnation-loading method.
The efficiency of the denitrogenation and dechlorobenzene in the temperature range of 150 to 210°C is higher than 90%, which reduces the cost of flue gas treatment. The catalyst components are environmentally friendly, the preparation process is simple, and the cost is low.
Smart Images

Figure CN119633803A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a preparation method and application of a coral-like low-temperature rare earth-based denitration and dechlorobenzene catalyst, belonging to the field of industrial flue gas purification. Background Art
[0002] As a waste treatment method, waste incineration has been widely used in many cities. Its advantages are that it can reduce the volume of waste, reduce the demand for landfills, and recover some energy. However, the process of waste incineration also produces a large amount of pollutants, including nitrogen oxides (NO x ), chlorobenzene compounds and other toxic substances have potential harm to the environment and human health. Therefore, studying how to effectively remove these harmful substances has become one of the key issues in the waste incineration process.
[0003] At present, the research on denitrification in the waste incineration industry mainly focuses on the selective catalytic reduction (SCR) technology, which is the most widely used denitrification technology. It uses a reducing agent (such as ammonia, urea, etc.) to react with NO under the action of a catalyst. x Reaction to generate nitrogen and water, mainly studying the selection of catalysts and the improvement of catalytic efficiency. Although there are many methods to remove chlorobenzene, such as adsorption, chemical reduction, catalytic oxidation, etc., catalytic oxidation has become an important research field due to its advantages of high efficiency and low cost. At present, the flue gas treatment in the waste incineration industry mainly adopts a segmented treatment method. Although it can efficiently remove nitrogen oxides and chlorobenzene, it will increase the flue gas treatment cost of the enterprise. Therefore, the research and development of low-temperature catalysts that can simultaneously remove nitrogen oxides and chlorobenzene is one of the important directions of flue gas treatment in the waste incineration industry. Summary of the invention
[0004] The purpose of the present invention is to propose a preparation method and application of a coral-like low-temperature rare earth-based denitrification and dechlorobenzene catalyst in view of the current situation and existing problems of insufficient catalytic activity of low-temperature denitrification and dechlorobenzene catalysts in flue gas in the waste incineration industry.
[0005] A coral-like low-temperature rare earth-based denitration and dechlorobenzene catalyst, which uses titanium dioxide as a carrier, a composite oxide of vanadium pentoxide and cerium dioxide as an active component, a composite oxide of tungsten oxide and molybdenum oxide as a co-catalyst, and porous activated carbon as a template, and is prepared by an ultrasonic foaming polymerization-template hydrothermal-impregnation loading method; wherein, based on the mass of the carrier, the mass percentage of the active component is 10-20%, the mass percentage of the co-catalyst is 10-20%, the mass ratio of vanadium pentoxide to cerium dioxide in the active component is 1:(0.5-1), and the mass ratio of tungsten oxide to molybdenum oxide in the co-catalyst is 1:(0.5-2).
[0006] A method for preparing the above-mentioned coral-like low-temperature rare earth-based denitrification and dechlorobenzene catalyst, the preparation method of the catalyst is as follows:
[0007] (1) Preparation of porous activated carbon template by foaming polymerization
[0008] The polymer monomer A and the polymer monomer B are mixed, and then placed in an oil bath for heating and ultrasonication, and then a cross-linking agent, an initiator and a foaming agent are added to form a mixed solution, and the solution is continuously stirred and ultrasonicated, and nitrogen is introduced during the stirring process to perform a foaming polymerization reaction, and after the reaction is completed, a porous polymer template is obtained by washing, and the porous polymer template is placed in a tubular atmosphere furnace and nitrogen is introduced to heat and carbonize to obtain a porous activated carbon template;
[0009] Wherein, polymer monomer A is vinyl alcohol, polymer monomer B is acrylic acid; the crosslinking agent is glutaraldehyde, the initiator is ammonium persulfate, and the foaming agent is azobisisobutyronitrile;
[0010] Preferably: during the polymerization reaction, nitrogen is output from the micron-sized pores;
[0011] (2) Preparation of titanium dioxide carrier
[0012] Weigh titanium salt, acetic acid, ethanol, deionized water and the porous activated carbon template obtained in step (1), mix them evenly and place them in an open beaker, then continue to stir the mixed solution at room temperature, after the titanium salt is hydrolyzed, place the mixed solution in a hydrothermal reactor for hydrothermal reaction, filter and dry after the reaction is completed, and calcine at high temperature to obtain a titanium dioxide carrier;
[0013] (3) Catalyst preparation
[0014] Vanadium salt, cerium salt, tungsten salt, molybdenum salt, monohydrated citric acid and deionized water are weighed and mixed evenly to obtain a precursor solution. The titanium dioxide carrier obtained in step (2) is then mixed and impregnated with the precursor solution obtained in step (3), and the mixture is placed in an oil bath. After drying, the mixture is calcined at high temperature to obtain a catalyst.
[0015] In the technical solution of the present invention: the mass ratio of the polymer monomer A and the polymer monomer B described in step (1) is 1: (0.5-2), and the mass ratio of the polymer monomer A, the crosslinking agent, the initiator, and the foaming agent is 1: (0.01-0.05): (0.01-0.05): (0.10-0.20).
[0016] In the technical solution of the present invention: in step (1), the temperature of the oil bath heating is 170-200° C., and the power of the ultrasound is 300-500W.
[0017] In the technical solution of the present invention: the rate of continuous stirring described in step (1) is 100-200 r / min, the rate of nitrogen introduction during the foaming polymerization reaction is 5-10 mL / min, and the time of the foaming polymerization reaction is 6-12 h.
[0018] In the technical solution of the present invention: the rate of introducing nitrogen during the heating carbonization in step (1) is 30-50 mL / min, the temperature of the heating carbonization is 600-700° C., and the heating rate is 10-20° C. / min.
[0019] In the technical scheme of the present invention: the titanium salt described in step (2) is tetrabutyl titanate or tetraethyl titanate, the mass ratio of titanium salt, acetic acid, ethanol, deionized water and porous activated carbon template is 1: (40-60): (20-40): (5-10): (1-5), and the stirring time is continuous for 24-48 hours.
[0020] In the technical scheme of the present invention: the temperature of the hydrothermal reaction described in step (2) is 140-160° C., and the hydrothermal time is 4-6 hours; the drying temperature is 80-100° C., and the drying time is 6-12 hours; the high-temperature calcination temperature is 500-600° C., and the high-temperature calcination time is 2-4 hours.
[0021] In the technical scheme of the present invention: the vanadium salt described in step (3) is ammonium metavanadate, the cerium salt is cerium chloride or cerium nitrate hexahydrate, the tungsten salt is ammonium metatungstate, the molybdenum salt is ammonium molybdate, the mass ratio of the vanadium salt, citric acid monohydrate and deionized water is 1: (10-20): (50-100), the temperature of the oil bath is 60-80°C, the time of the oil bath is 6-12h, the temperature of the high-temperature roasting is 500-600°C, and the time of the high-temperature roasting is 2-4h.
[0022] In the technical solution of the present invention: the catalyst is used in the denitration and dechlorobenzene removal of low-temperature flue gas in the waste incineration industry.
[0023] The experimental conditions for evaluating the activity of the catalyst of the present invention are as follows: 1 mL of a catalyst of 20 to 40 mesh is taken, poured into a quartz tube with an inner diameter of 6 mm, fixed with quartz wool and wire mesh, and the quartz tube is placed in a tubular furnace, and the actual temperature of the catalytic reaction is adjusted by controlling the heating temperature of the tubular furnace. Intake gas components: NO (500 ppm), NH3 (500 ppm), O2 (11 vol.%), chlorobenzene (200 ppm), and the rest are N2, the total gas flow rate is 500 mL / min, the temperature is controlled at 90 to 210° C., and the temperature is kept stable for 30 minutes at every 30° C. The NO concentration is measured by a Laoying 3021 portable carbon emission monitor, and the chlorobenzene concentration is measured by gas chromatography. The catalyst denitration and dechlorobenzene efficiency in the temperature range of 150 to 210° C. is higher than 90%.
[0024] Beneficial effects:
[0025] (1) The present invention not only utilizes the chemical method of oil bath decomposition of azobisisobutyronitrile to generate foam, but also utilizes the physical method of introducing nitrogen into the solution through the micron-sized pores of a rubber hose to form micron-sized bubbles, and utilizes ultrasound to evenly disperse and dissolve the bubbles generated by the physical and chemical combined methods in the solution, thereby forming micro-nano bubbles, and then utilizes the micro-nano bubbles to occupy the sites of polymerization and cross-linking of vinyl alcohol and acrylic acid, thereby forming uniformly dispersed pores, and finally forming a porous polymer template with micro-nano pores;
[0026] (2) The porous polymer template forms a porous activated carbon template after high-temperature carbonization, and then titanium dioxide is grown on the surface of the porous activated carbon by the template hydrothermal method, and finally the template is eliminated by high-temperature roasting. Compared with conventional activated carbon, although the conventional activation method can also produce porous activated carbon with a large specific surface area, its pore structure is affected by the distribution of chemical activators such as sodium hydroxide, making the pore structure uneven and difficult to predict. In addition, the conventional chemical activation method uses highly corrosive chemical solvents such as sodium hydroxide, which will corrode instruments and equipment during actual application, making it difficult to apply in large-scale engineering.
[0027] (3) The present invention adopts a porous activated carbon template to prepare a coral-like catalyst, whose surface has a rich synaptic structure, which is conducive to the full exposure of the active sites, thereby increasing the contact possibility between the active sites and the reaction molecules and enhancing the low-temperature denitrification and dechlorobenzene performance of the catalyst;
[0028] (4) The present invention uses titanium dioxide as a carrier, vanadium oxide and cerium oxide as active components, and tungsten oxide and molybdenum oxide as co-catalysts, so that the catalyst has the specific surface area and mechanical strength of titanium dioxide, the excellent redox performance and oxygen storage and release performance of vanadium oxide and cerium oxide, and the rich acid sites of tungsten oxide and molybdenum oxide, thereby ensuring its low-temperature denitrification and dechlorobenzene performance.
[0029] Therefore, the catalyst prepared by the present invention not only has excellent low-temperature flue gas denitration and dechlorobenzene performance, but the application of rare earth-based catalysts can effectively promote the high-value and efficient utilization of rare earth elements in the field of environmental protection in my country, and the catalyst component is environmentally friendly, simple in preparation process, low in cost, high in cost performance, and has strong application and promotion value. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is the SEM image of the catalyst prepared in Example 1;
[0031] Figure 2 This is the SEM image of the catalyst prepared in Comparative Example 1;
[0032] Figure 3The NO removal performance diagram of the catalysts prepared in Example 1-2 and Comparative Example 1-2;
[0033] Figure 4 This is a performance diagram of chlorobenzene removal of the catalysts prepared in Example 1-2 and Comparative Example 1-2. DETAILED DESCRIPTION
[0034] The present invention is further described below in conjunction with examples. The examples are implemented on the premise of the technical solution of the present invention, and detailed implementation methods and specific operating processes are given, but the protection scope of the present invention is not limited to the following examples.
[0035] Example 1
[0036] (1) Preparation of porous activated carbon template by foaming polymerization
[0037] The mass flow meter and the nitrogen cylinder were connected to one end of a rubber hose (with an inner pore diameter of 6 mm), and the air outlet at the other end of the rubber hose was sealed with NQ-704 room temperature curing silicone rubber. At the same time, 20 air holes were pierced with a metal needle (with a needle diameter of 0.2 mm) for standby use. 20.000 g of vinyl alcohol and 10.000 g of acrylic acid were weighed, mixed and stirred evenly and placed in a beaker. The beaker was placed in an ultrasonic oil bath pot and heated at 170°C in an oil bath and ultrasonicated (ultrasonic power of 300 W). Then, 0.200 g of glutaraldehyde, 0.200 g of ammonium persulfate and 2.000 g of azobisisobutyronitrile were added to form a mixed solution and Continuously stir (stirring rate is 100r / min) and ultrasonic (ultrasonic power is 300W), during the continuous stirring process, place a rubber hose with micron-sized pores at the bottom of the mixed solution in the beaker, introduce nitrogen (nitrogen introduction rate is 5mL / min) to carry out foaming polymerization reaction for 6h, after the foaming polymerization reaction is completed, wash with ethanol to obtain a porous polymer template, place the porous polymer template in a tubular atmosphere furnace, introduce nitrogen to heat and carbonize (nitrogen introduction rate is 30mL / min, carbonization temperature is 600℃, heating rate is 10℃ / min), and obtain a porous activated carbon template;
[0038] (2) Preparation of titanium dioxide carrier
[0039] Weigh 8.522 g of tetrabutyl titanate, 340.880 g of acetic acid, 170.440 g of ethanol, 42.610 g of deionized water and 8.522 g of the porous activated carbon template obtained in step (1), mix them evenly and place them in an open beaker, then continue to stir the mixed solution at room temperature for 24 hours, after the titanium salt is hydrolyzed, place the mixed solution in a hydrothermal reactor for hydrothermal reaction at 140° C. for 6 hours, filter after the reaction, place in an oven for drying at 80° C. for 12 hours, and then place in a muffle furnace for high-temperature roasting at 500° C. for 4 hours to obtain a titanium dioxide carrier;
[0040] (3) Catalyst preparation
[0041] 0.171 g of ammonium metavanadate, 0.096 g of cerium chloride, 0.141 g of ammonium metatungstate, 0.091 g of ammonium molybdate, 1.710 g of citric acid monohydrate and 8.550 g of deionized water were weighed and mixed to obtain a precursor solution. Then, the titanium dioxide carrier obtained in step (2) was mixed and impregnated with the precursor solution obtained in step (3), and placed in an oil bath at 60° C. for 12 h. After drying, the catalyst was calcined at 500° C. for 4 h to obtain a catalyst (based on the mass of the carrier, the mass percentage of the active component is 10%, the mass percentage of the co-catalyst is 10%, the mass ratio of vanadium pentoxide to cerium dioxide in the active component is 1:0.5, the mass ratio of tungsten oxide to molybdenum oxide in the co-catalyst is 1:0.5, and the SEM image of the catalyst is as follows: Figure 1 shown);
[0042] (4) Catalytic activity test
[0043] Take 1mL of 20-40 mesh catalyst, pour it into a quartz tube with an inner diameter of 6mm, fix it with quartz wool and wire mesh, put the quartz tube in a tube furnace, and adjust the actual temperature of the catalytic reaction by controlling the heating temperature of the tube furnace. Intake components: NO (500ppm), NH3 (500ppm), O2 (11vol.%), chlorobenzene (200ppm), and the rest are N2, the total gas flow is 500mL / min, the temperature is controlled at 90-210℃, stay stable for 30min every 30℃, use Laoying 3021 portable carbon emission monitor to measure NO concentration, gas chromatography to measure chlorobenzene concentration, and the catalyst denitrification and dechlorobenzene efficiency in the temperature range of 150-210℃ is higher than 90%.
[0044] Example 2
[0045] (1) Preparation of porous activated carbon template by foaming polymerization
[0046] The mass flow meter and the nitrogen cylinder were connected to one end of a rubber hose (with an inner pore diameter of 8 mm), and the air outlet at the other end of the rubber hose was sealed with NQ-704 room temperature curing silicone rubber. At the same time, 30 air holes were pierced with a metal needle (with a needle diameter of 0.3 mm) for standby use. 20.000 g of vinyl alcohol and 40.000 g of acrylic acid were weighed, mixed and stirred evenly, and placed in a beaker. The beaker was placed in an ultrasonic oil bath pot and heated at 200°C in an oil bath and ultrasonicated (ultrasonic power of 500 W). Then, 1.000 g of glutaraldehyde, 1.000 g of ammonium persulfate and 4.000 g of azobisisobutyronitrile were added to form a mixed solution and maintained for 2 hours. Continue stirring (stirring rate is 200r / min) and ultrasound (ultrasonic power is 500W), during the continuous stirring process, place a rubber hose with micron-sized pores at the bottom of the mixed solution in the beaker, introduce nitrogen (nitrogen introduction rate is 10mL / min) to carry out foaming polymerization reaction for 12h, after the foaming polymerization reaction is completed, wash with ethanol to obtain a porous polymer template, place the porous polymer template in a tubular atmosphere furnace, introduce nitrogen to heat and carbonize (nitrogen introduction rate is 50mL / min, carbonization temperature is 700℃, heating rate is 20℃ / min), and obtain a porous activated carbon template;
[0047] (2) Preparation of titanium dioxide carrier
[0048] Weigh 5.712 g of tetraethyl titanate, 342.720 g of acetic acid, 228.480 g of ethanol, 57.120 g of deionized water and 28.560 g of the porous activated carbon template obtained in step (1), mix them evenly and place them in an open beaker, then continue to stir the mixed solution at room temperature for 48 hours, after the titanium salt is hydrolyzed, place the mixed solution in a hydrothermal reactor for hydrothermal reaction at 160° C. for 4 hours, filter after the reaction, place in an oven for drying at 100° C. for 6 hours, and then place in a muffle furnace for high-temperature roasting at 600° C. for 2 hours to obtain a titanium dioxide carrier;
[0049] (3) Catalyst preparation
[0050] Weigh 0.257 g of ammonium metavanadate, 0.505 g of cerium nitrate hexahydrate, 0.141 g of ammonium metatungstate, 0.364 g of ammonium molybdate, 5.140 g of citric acid monohydrate and 25.700 g of deionized water and mix them evenly to obtain a precursor solution; then, the titanium dioxide carrier obtained in step (2) is mixed and impregnated with the precursor solution obtained in step (3), and placed in an oil bath at 80° C. for 6 h; after drying, the catalyst is calcined at 600° C. for 2 h to obtain a catalyst (based on the mass of the carrier, the mass percentage of the active component is 20%, the mass percentage of the co-catalyst is 20%, the mass ratio of vanadium pentoxide to cerium dioxide in the active component is 1:1, and the mass ratio of tungsten oxide to molybdenum oxide in the co-catalyst is 1:2);
[0051] (4) Catalytic activity test
[0052] Take 1mL of 20-40 mesh catalyst, pour it into a quartz tube with an inner diameter of 6mm, fix it with quartz wool and wire mesh, put the quartz tube in a tube furnace, and adjust the actual temperature of the catalytic reaction by controlling the heating temperature of the tube furnace. Intake components: NO (500ppm), NH3 (500ppm), O2 (11vol.%), chlorobenzene (200ppm), and the rest are N2, the total gas flow is 500mL / min, the temperature is controlled at 90-210℃, stay stable for 30min every 30℃, use Laoying 3021 portable carbon emission monitor to measure NO concentration, gas chromatography to measure chlorobenzene concentration, and the catalyst denitrification and dechlorobenzene efficiency in the temperature range of 150-210℃ is higher than 90%.
[0053] Example 3
[0054] (1) Preparation of porous activated carbon template by foaming polymerization
[0055] The mass flow meter and the nitrogen cylinder were connected to one end of a rubber hose (with an inner pore diameter of 8 mm), and the air outlet at the other end of the rubber hose was sealed with NQ-704 room temperature curing silicone rubber. At the same time, 30 air holes were pierced with a metal needle (with a needle diameter of 0.3 mm) for standby use. 20.000 g of vinyl alcohol and 40.000 g of acrylic acid were weighed, mixed and stirred evenly and placed in a beaker. The beaker was placed in an ultrasonic oil bath pot and heated at 200°C and ultrasonicated (ultrasonic power of 500 W). Then, 1.000 g of glutaraldehyde, 1.000 g of ammonium persulfate and 4.000 g of azobisisobutyronitrile were added to form a mixed solution and maintained for 2 hours. Continue stirring (stirring rate is 200r / min) and ultrasound (ultrasonic power is 500W), during the continuous stirring process, place a rubber hose with micron-sized pores at the bottom of the mixed solution in the beaker, introduce nitrogen (nitrogen introduction rate is 10mL / min) to carry out foaming polymerization reaction for 12h, after the foaming polymerization reaction is completed, wash with ethanol to obtain a porous polymer template, place the porous polymer template in a tubular atmosphere furnace, introduce nitrogen to heat and carbonize (nitrogen introduction rate is 50mL / min, carbonization temperature is 700℃, heating rate is 20℃ / min), and obtain a porous activated carbon template;
[0056] (2) Preparation of titanium dioxide carrier
[0057] Weigh 5.712 g of tetraethyl titanate, 342.720 g of acetic acid, 228.480 g of ethanol, 57.120 g of deionized water and 28.560 g of the porous activated carbon template obtained in step (1), mix them evenly and place them in an open beaker, then continue to stir the mixed solution at room temperature for 48 hours, after the titanium salt is hydrolyzed, place the mixed solution in a hydrothermal reactor for hydrothermal reaction at 150° C. for 4 hours, filter after the reaction, place in an oven for drying at 100° C. for 6 hours, and then place in a muffle furnace for high-temperature roasting at 500° C. for 2 hours to obtain a titanium dioxide carrier;
[0058] (3) Catalyst preparation
[0059] Weigh 0.257 g of ammonium metavanadate, 0.505 g of cerium nitrate hexahydrate, 0.213 g of ammonium metatungstate, 0.272 g of ammonium molybdate, 5.140 g of citric acid monohydrate and 25.700 g of deionized water and mix them evenly to obtain a precursor solution; then, the titanium dioxide carrier obtained in step (2) is mixed and impregnated with the precursor solution obtained in step (3), and placed in an oil bath at 80° C. for 6 h; after drying, the catalyst is calcined at 500° C. for 2 h to obtain a catalyst (based on the mass of the carrier, the mass percentage of the active component is 10%, the mass percentage of the co-catalyst is 20%, the mass ratio of vanadium pentoxide to cerium dioxide in the active component is 1:1, and the mass ratio of tungsten oxide to molybdenum oxide in the co-catalyst is 1:1);
[0060] (4) Catalytic activity test
[0061] Take 1mL of 20-40 mesh catalyst, pour it into a quartz tube with an inner diameter of 6mm, fix it with quartz wool and wire mesh, put the quartz tube in a tube furnace, and adjust the actual temperature of the catalytic reaction by controlling the heating temperature of the tube furnace. Intake components: NO (500ppm), NH3 (500ppm), O2 (11vol.%), chlorobenzene (200ppm), and the rest are N2, the total gas flow is 500mL / min, the temperature is controlled at 90-210℃, stay stable for 30min every 30℃, use Laoying 3021 portable carbon emission monitor to measure NO concentration, gas chromatography to measure chlorobenzene concentration, and the catalyst denitrification and dechlorobenzene efficiency in the temperature range of 150-210℃ is higher than 90%.
[0062] Comparative Example 1
[0063] (1) Preparation of carrier
[0064] Except that the porous activated carbon template is not used in the catalyst preparation, other conditions are the same as those in Example 1;
[0065] (2) Catalytic activity test
[0066] Take 1mL of 20-40 mesh catalyst, pour it into a quartz tube with an inner diameter of 6mm, fix it with quartz wool and wire mesh, put the quartz tube in a tube furnace, and adjust the actual temperature of the catalytic reaction by controlling the heating temperature of the tube furnace. Intake components: NO (500ppm), NH3 (500ppm), O2 (11vol.%), chlorobenzene (200ppm), and the rest are N2. The total gas flow rate is 500mL / min, and the temperature is controlled at 90-210℃. Stay stable for 30min every 30℃. Use Laoying 3021 portable carbon emission monitor to measure NO concentration, and gas chromatography to measure chlorobenzene concentration. The catalyst denitrification efficiency at 150℃ is 43.6%, and the dechlorobenzene efficiency is 62.7%; (3) Comparative effect
[0067] Compared with Example 1, the catalyst was prepared without using a porous activated carbon template. Figure 2 The prepared catalyst is irregular nanoparticles, and the number of synaptic structure-like particles is significantly reduced, resulting in a decrease in the proportion of exposed active sites, thereby reducing the low-temperature catalytic activity.
[0068] Comparative Example 2
[0069] (1) Preparation of catalyst
[0070] Except that the rubber hose was not used to introduce nitrogen during catalyst preparation, other conditions were the same as those in Example 2;
[0071] (2) Catalytic activity test
[0072] Take 1mL of 20-40 mesh catalyst, pour it into a quartz tube with an inner diameter of 6mm, fix it with quartz wool and wire mesh, put the quartz tube in a tubular furnace, and adjust the actual temperature of the catalytic reaction by controlling the heating temperature of the tubular furnace. Intake components: NO (500ppm), NH3 (500ppm), O2 (11vol.%), chlorobenzene (200ppm), and the rest are N2. The total gas flow rate is 500mL / min, and the temperature is controlled at 90-210℃. Stay stable for 30min every 30℃. Use Laoying 3021 portable carbon emission monitor to measure NO concentration, and gas chromatography to measure chlorobenzene concentration. The catalyst denitrification efficiency at 150℃ is 61.3%, and the dechlorobenzene efficiency is 73.1%; (3) Comparative effect
[0073] Compared with Example 2, nitrogen is not introduced through a rubber hose during catalyst preparation. Although bubbles can be obtained by decomposition of azobisisobutyronitrile for foaming, the number of pores is not as good as that in Example 2, and the synaptic structure of the prepared catalyst may be lower, resulting in reduced denitration and dechlorobenzene activity.
Claims
1. A coral-like low-temperature rare earth-based denitrification and dechlorobenzene catalyst, characterized in that: The catalyst uses titanium dioxide as a carrier, a composite oxide of vanadium pentoxide and cerium dioxide as an active component, a composite oxide of tungsten oxide and molybdenum oxide as a co-catalyst, and porous activated carbon as a template agent, and is prepared by an ultrasonic foaming polymerization-template hydrothermal-impregnation loading method; wherein, based on the mass of the carrier, the mass percentage of the active component is 10-20%, the mass percentage of the co-catalyst is 10-20%, the mass ratio of vanadium pentoxide to cerium dioxide in the active component is 1:(0.5-1), and the mass ratio of tungsten oxide to molybdenum oxide in the co-catalyst is 1:(0.5-2).
2. A method for preparing the coral-like low-temperature rare earth-based denitrification and dechlorobenzene catalyst according to claim 1, characterized in that: The preparation method of the catalyst is as follows: (1) Preparation of porous activated carbon template by foaming polymerization The polymer monomer A and the polymer monomer B are mixed, and then placed in an oil bath for heating and ultrasonication, and then a cross-linking agent, an initiator and a foaming agent are added to form a mixed solution, and the solution is continuously stirred and ultrasonicated, and nitrogen is introduced during the stirring process to perform a foaming polymerization reaction, and after the reaction is completed, a porous polymer template is obtained by washing, and the porous polymer template is placed in a tubular atmosphere furnace and nitrogen is introduced to heat and carbonize to obtain a porous activated carbon template; Wherein, polymer monomer A is vinyl alcohol, polymer monomer B is acrylic acid; the crosslinking agent is glutaraldehyde, the initiator is ammonium persulfate, and the foaming agent is azobisisobutyronitrile; Preferably: during the polymerization reaction, nitrogen is output from the micron-sized pores; (2) Preparation of titanium dioxide carrier Weigh titanium salt, acetic acid, ethanol, deionized water and the porous activated carbon template obtained in step (1), mix them evenly and place them in an open beaker, then continue to stir the mixed solution at room temperature, after the titanium salt is hydrolyzed, place the mixed solution in a hydrothermal reactor for hydrothermal reaction, filter and dry after the reaction is completed, and calcine at high temperature to obtain a titanium dioxide carrier; (3) Catalyst preparation Vanadium salt, cerium salt, tungsten salt, molybdenum salt, monohydrated citric acid and deionized water are weighed and mixed evenly to obtain a precursor solution. The titanium dioxide carrier obtained in step (2) is then mixed and impregnated with the precursor solution obtained in step (3), and the mixture is placed in an oil bath. After drying, the mixture is calcined at high temperature to obtain a catalyst.
3. The preparation method according to claim 1, characterized in that: The mass ratio of polymer monomer A to polymer monomer B in step (1) is 1:(0.5-2), and the mass ratio of polymer monomer A, crosslinking agent, initiator and foaming agent is 1:(0.01-0.05):(0.01-0.05):(0.10-0.20).
4. The preparation method according to claim 1, characterized in that: In step (1), the temperature of the oil bath heating is 170-200° C., and the power of the ultrasound is 300-500W.
5. The preparation method according to claim 1, characterized in that: The continuous stirring rate in step (1) is 100-200 r / min, the rate of nitrogen introduction during the foaming polymerization reaction is 5-10 mL / min, and the foaming polymerization reaction time is 6-12 h.
6. The preparation method according to claim 1, characterized in that: The rate of introducing nitrogen during the heating carbonization in step (1) is 30-50 mL / min, the temperature of the heating carbonization is 600-700° C., and the heating rate is 10-20° C. / min.
7. The preparation method according to claim 1, characterized in that: The titanium salt described in step (2) is tetrabutyl titanate or tetraethyl titanate, and the mass ratio of the titanium salt, acetic acid, ethanol, deionized water and porous activated carbon template is 1: (40-60): (20-40): (5-10): (1-5), and the stirring time is continuous for 24-48 hours.
8. The preparation method according to claim 1, characterized in that: The temperature of the hydrothermal reaction in step (2) is 140-160° C., and the hydrothermal time is 4-6 hours; the drying temperature is 80-100° C., and the drying time is 6-12 hours; the high-temperature calcination temperature is 500-600° C., and the high-temperature calcination time is 2-4 hours.
9. The preparation method according to claim 1, characterized in that: The vanadium salt described in step (3) is ammonium metavanadate, the cerium salt is cerium chloride or cerium nitrate hexahydrate, the tungsten salt is ammonium metatungstate, the molybdenum salt is ammonium molybdate, the mass ratio of the vanadium salt, citric acid monohydrate and deionized water is 1:(10-20):(50-100), the temperature of the oil bath is 60-80°C, the time of the oil bath is 6-12h, the temperature of the high-temperature roasting is 500-600°C, and the time of the high-temperature roasting is 2-4h.
10. Use of the catalyst according to claim 1 in the denitration and dechlorobenzene removal of low-temperature flue gas in the waste incineration industry.